The Effect Of Accrual-Based Psap, Accounting Policy, And Information Technology On The Quality Of Lkpd In Binjai City - Fhikry Ahmad Halomoan Siregar; Selvi Aristantya; Adek Apriyandi (Institute of Computer Science (IOCS), 2022)
This study aims to determine and analyze the effect of the application of accrual-based government accounting standards, accounting policies, and the use of information technology on the quality of local government financial reports in the city of Binjai. This type of research is causal and the object of this research is Binjai City. The data used are primary data obtained from questionnaires with a total sample of 69 respondents. Research data Using a quantitative approach and data analysis using a simple regression analysis model. The results showed that the application of accrual-based government accounting standards, accounting policies, and the use of information technology had an effect on the quality of the financial statements of the local government of the city of Binjai.